2003
DOI: 10.1001/archsurg.138.12.1383
|View full text |Cite
|
Sign up to set email alerts
|

Extended Esophagectomy With 3-Field Lymph Node Dissection for Esophageal Cancer

Abstract: To review the surgical outcomes of extended esophagectomy with 3-field lymph node dissection (3FLND) for esophageal cancer.Data Sources: Only articles written in English and written after 1980 were selected from MEDLINE. The following terms were identified: 3FLND, extensive or extended lymph node dissection (lymphadenectomy), radical lymph node dissection, cervical lymph node dissection, and extended or radical esophagectomy in esophageal cancer.Study Selection: There were no exclusion criteria for published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 62 publications
1
42
0
7
Order By: Relevance
“…Thus using hoarseness alone to diagnose RLN palsy will underestimate this complication. A review of three-field lymphadenectomy in Japan yielded an overall RLN palsy rate of 27% (20), some studies have shown up to 60% (1,21). In a recent detailed study on 299 patients, 60% developed RLN palsy, bilateral in 33%, right RLN in 8% and left in 59%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus using hoarseness alone to diagnose RLN palsy will underestimate this complication. A review of three-field lymphadenectomy in Japan yielded an overall RLN palsy rate of 27% (20), some studies have shown up to 60% (1,21). In a recent detailed study on 299 patients, 60% developed RLN palsy, bilateral in 33%, right RLN in 8% and left in 59%.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there's also some series showed the similar surgical outcomes in Table 2 with the 5-year OS rates range from 41.9% to 73.2% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)51), which is better than the outcome of 2-FL in Table 4 (14,16,(22)(23)(24). The mortality rates maintained between 1.2% and 10.4%, which is lower than that in 2-FL (14,16,(22)(23)(24)(25).…”
Section: Clinical Outcomesmentioning
confidence: 93%
“…Tachibana et al (51) has once reviewed the surgical outcomes of extended esophagectomy with 3-field lymph node dissection after 1980 and made the conclusion that the extended esophagectomy with 3-FL would be a safe treatment with low morbidity and acceptable mortality rates. Meanwhile, there's also some series showed the similar surgical outcomes in Table 2 with the 5-year OS rates range from 41.9% to 73.2% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)51), which is better than the outcome of 2-FL in Table 4 (14,16,(22)(23)(24).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…El 10% de los tumores de tercio inferior presenta compromiso linfonodal en el tercio torácico superior y el 31% de los de tercio torácico superior presentan compromiso linfonodal perigástrico 29 . En una revisión del año 2003 sobre diferentes trabajos publicados hasta ese momento, se concluyó que la linfadenectomía en 3 campos lograba aumentar la sobrevida y disminuir la recurrencia locoregional, pero debía ser realizada en manos experimentadas 39 . En Chile, un grupo de cirujanos son proclives a efectuar linfadenectomía, juega un rol relevante en el tratamiento del carcinoma espinocelular de esófago pero la evidencia apoya la esofaguectomía subtotal con linfadenectomía en tres campos aún es discutible 12,29 .…”
Section: Linfadenectomía En Cáncer De Esófagounclassified
“…Recientemente hay excelentes reportes dando cuenta de los resultados en cuanto a sobrevida y la tendencia es aceptar que la cirugía mini-invasiva no compromete los resultados oncológicos [65][66][67][68][69] . Desde el advenimiento de la cirugía mínimamen-te invasiva, la adecuada resección oncológica en comparación a la cirugía abierta ha sido cuestionada en relación a los márgenes de resección, la completa linfadenectomía, la correcta etapificación postoperatoria y la sobrevida a largo plazo 37,39 . Todas las resecciones oncológicas potencialmente curativas, requieren de un margen completo de resección del tumor primario R0, siendo éste el factor de mayor importancia en la sobrevida de los pacientes.…”
unclassified